2019
DOI: 10.1016/j.jstrokecerebrovasdis.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Benefit of Twendee X in Alzheimer's Disease Transgenic Mice with Chronic Cerebral Hypoperfusion

Abstract: Abbreviations used: ameriod constrictors (ACs); Alzheimer's disease (AD); amyloid-β (Aβ); bilateral common carotid arteries (BCCAs); bovine serum albumin (BSA); cerebral blood flow (CBF); chronic cerebral hypoperfusion (CCH); cortex (CTX); dentate gyrus (DG); hippocampus (HI); months (M); phosphate-buffered saline (PBS); paraformaldehyde (PFA); subiculum (Sub); thalamus (TH); Twendee X (TwX); wild type (WT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…The therapeutic effect of TwX was also examined in nude mice that underwent inoculation of colon or gastric cancer cells: TwX reduced tumor growth, increased antioxidants measured by the d-ROMs test, and reduced natural killer cell activity, suggesting that TwX significantly reduced tumor growth and inhibited metastasis by reducing oxidative stress [107]. In ischemic stroke model mice, we demonstrated that pretreatment of TwX (20 mg/kg/d for 14 days) reduced infarct size as well as the expression of both oxidative stress markers such as 8-OHdG, 4-HNE and Nε-(carboxymethyl) lysine (an advanced glycation end product) and inflammatory markers such as Iba-1, tumor necrosis factor α (TNF-α) and monocyte chemotactic protein [108,109].…”
Section: Twendee Xmentioning
confidence: 97%
“…The therapeutic effect of TwX was also examined in nude mice that underwent inoculation of colon or gastric cancer cells: TwX reduced tumor growth, increased antioxidants measured by the d-ROMs test, and reduced natural killer cell activity, suggesting that TwX significantly reduced tumor growth and inhibited metastasis by reducing oxidative stress [107]. In ischemic stroke model mice, we demonstrated that pretreatment of TwX (20 mg/kg/d for 14 days) reduced infarct size as well as the expression of both oxidative stress markers such as 8-OHdG, 4-HNE and Nε-(carboxymethyl) lysine (an advanced glycation end product) and inflammatory markers such as Iba-1, tumor necrosis factor α (TNF-α) and monocyte chemotactic protein [108,109].…”
Section: Twendee Xmentioning
confidence: 97%
“…It has been reported that chronic cerebral hypoperfusion (CCH) induces oxidative stress and neuroinflammation, potentially contributing to the progression of neurodegenerative diseases [70,71]. Thus, recent studies have examined whether an antioxidant supplement, Twendee X (TwX), exhibits beneficial effects in a mouse model of AD with CCH [72,73]. TwX contains the antioxidants coenzyme Q10, niacin amid, L-cystine, ascorbic acid, succinic acid, fumaric acid, L-glutamine, and riboflavin [72][73][74].…”
Section: Preclinical Findings Obtained By Twendee X Administrationmentioning
confidence: 99%
“…Thus, recent studies have examined whether an antioxidant supplement, Twendee X (TwX), exhibits beneficial effects in a mouse model of AD with CCH [72,73]. TwX contains the antioxidants coenzyme Q10, niacin amid, L-cystine, ascorbic acid, succinic acid, fumaric acid, L-glutamine, and riboflavin [72][73][74]. One study administered TwX by oral gavage to APP23 mice, which overexpress the human APP Swedish mutant gene, that were treated with ameroid constrictors on bilateral common carotid arteries to induce CCH development [72,73].…”
Section: Preclinical Findings Obtained By Twendee X Administrationmentioning
confidence: 99%
See 2 more Smart Citations